Synergistic improvement of strength and electrical conductivity in Cu–Cr–Zr alloys through prestrain-assisted friction stir processing - Yijun Li; Jinghua Zhang; Ruidong Fu; Junhao Wang; Hongyan Lv; Haizhi Xing (Journal of Materials Research and Technology, 2023)
The objective of this study is to investigate the effects of prestrain-assisted friction stir processing and subsequent aging heat treatment on the microstructural evolution and performance of copper-chromium-zirconium alloys. The findings indicated that prestrain, generated through cold rolling before friction stir processing, considerably affected grain refinement and enhanced the mechanical properties and electrical conductivity in the processing zone. The prestrain not only decreased the activation energy of dynamic restoration and precipitation in the processing zone, but also strengthened the “constraint effect” of the base metals to the processing zone. This effectively reduced the width of micro-bands and promoted nanocrystalline formation in the processing zone. Furthermore, dynamic precipitation resulted in higher thermal stability of the microstructure in the processing zone during subsequent aging heat treatment. Thus, the synergistic improvement of the mechanical properties and electrical conductivity of copper-chromium-zirconium alloys was successfully achieved.